Free radical production by azomethine H: Effects on pancreatic and hepatic tissues - Novelli, E. L B; Silva, A. M M; Monteiro, J. P.; Sacomani, L. B.; Novellif, J. L V B [UNESP] (Taylor & Francis, 1997)
The antimalarial properties of azomethine H represent the basis for its use as a chemotherapeutic agent. This work was carried out in order to verify the biological side effects of azomethine H and to clarify the contribution of reactive oxygen species (ROS) in this process. It was shown that azomethine H increased serum activities of amylase, alanine transaminase (ALT) and the TEARS concentrations, in rats. No changes were observed in glutathione peroxidase and catalase activities. The drug-induced tissue damage might be due to superoxide radicals (O-2(.-)), since Cu-Zn superoxide dismutase activities were increased by azomethine I-I treatment. This study allows tentative conclusions to be drawn regarding which reactive oxygen metabolites play a role in azomethine H activity. We concluded that (O-2(.-)) maybe produced as a mediator of azomethine H action.
Keywords: Azomethine H; Cu-Zn superoxide dismutase; Glutathione peroxidase; Superoxide radical; Toxicity; alanine aminotransferase; amylase; antimalarial agent; azomethine h; catalase; copper zinc superoxide dismutase; free radical; glutathione peroxidase; reactive oxygen metabolite; superoxide; thiobarbituric acid reactive substance; unclassified drug; alanine aminotransferase blood level; amylase blood level; animal experiment; animal tissue; controlled study; dose response; enzyme activity; intraperitoneal drug administration; male; nonhuman; rat; tissue injury; Alanine Transaminase; Amylases; Animals; Antimalarials; Catalase; Dose-Response Relationship, Drug; Free Radicals; Glutathione Peroxidase; Liver; Male; Naphthalenesulfonates; Pancreas; Rats; Rats, Wistar; Reactive Oxygen Species; Superoxide Dismutase; Superoxides; Thiobarbituric Acid Reactive Substances; Thiosemicarbazones; Animalia